PENGARUH MEDIA TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PAKCOY (Brassica rapa L.) - Angela Marici Sri Intan Pare; I Putu Sujana; Ni Putu Eka Pratiwi; I Made Suryana; Komang Dean Ananda (Agrofarm: Jurnal Agroteknologi, 2023)
This study entitled the effect of planting media on the growth and yield of pakcoy (Brasicca rapa L). The effect of organic fertilizer is treated to increase growth and yield, especially pakcoy. The purpose of this study was to determine the effect of organic fertilizer on the growth and yield of pakcoy and to determine the concentration and variety of organic fertilizers as an optimal type of organic fertilizer planting medium on the growth and yield of pakcoy. This study used a randomized block design research method (DRM) using various kinds of organic fertilizers, namely cow manure, goat manure, chicken manure, and mixed manure for cows, goats and chicken manure (P0-P5). The author collects data from the parameters of plant height, leaf area. Leaf length, total fresh weight of plants, and total dry weight of plants. Data is taken from each parameter. The results of this study on all parameters gave good results, and for the planting media the best results were using manure mixed with cow manure, goat manure, and chicken manure (P4).